Stone Age Yersinia pestis genomes shed light on the early evolution, diversity, and ecology of plague - Andrades Valtueña, Aida; Neumann, Gunnar U; Spyrou, Maria A; Musralina, Lyazzat; Aron, Franziska; Beisenov, Arman; Belinskiy, Andrey B; Bos, Kirsten I; Buzhilova, Alexandra; Conrad, Matthias; Djansugurova, Leyla B; Dobeš, Miroslav; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
The bacterial pathogen Yersinia pestis gave rise to devastating outbreaks throughout human history, and ancient DNA evidence has shown it afflicted human populations as far back as the Neolithic. Y. pestis genomes recovered from the Eurasian Late Neolithic/Early Bronze Age (LNBA) period have uncovered key evolutionary steps that led to its emergence from a Yersinia pseudotuberculosis-like progenitor; however, the number of reconstructed LNBA genomes are too few to explore its diversity during this critical period of development. Here, we present 17 Y. pestis genomes dating to 5,000 to 2,500 y BP from a wide geographic expanse across Eurasia. This increased dataset enabled us to explore correlations between temporal, geographical, and genetic distance. Our results suggest a nonflea-adapted and potentially extinct single lineage that persisted over millennia without significant parallel diversification, accompanied by rapid dispersal across continents throughout this period, a trend not observed in other pathogens for which ancient genomes are available. A stepwise pattern of gene loss provides further clues on its early evolution and potential adaptation. We also discover the presence of the flea-adapted form of Y. pestis in Bronze Age Iberia, previously only identified in in the Caucasus and the Volga regions, suggesting a much wider geographic spread of this form of Y. pestis. Together, these data reveal the dynamic nature of plague’s formative years in terms of its early evolution and ecology.
Keywords: Animals; Yersinia pestis; Plague; DNA, Ancient; ancient DNA; Animal Husbandry; Human Migration; lidé; Genome, Bacterial; genom bakteriální; Genetic Variation; Phylogeny; mor; plague; dějiny starověku; zvířata; migrace lidstva; chov zvířat; starobylá DNA; fylogeneze; genetická variace; History, Ancient; Humans